Precautionary Reserves : An Application to Bolivia - Valencia, Fabian (IMF Working Papers; Working Paper ;, 2010)
Using precautionary savings models we compute levels of optimal reserves for Bolivia. Because of Bolivia's reliance on commodity exports and little integration with capital markets, we focus on current account shocks as the key balance of payments risk. These models generate an optimal level of net foreign assets ranging from 29 to 37 percent of GDP. For comparison purposes, we contrasted these results with standard rule of thumb measures of reserve adequacy, which in the case of Bolivia resulted in substantially lower levels of adequate reserves. These differing results emphasize the need to appropriately account for country-specific risks in order to derive adequate measures of reserve buffers.